2023
DOI: 10.1039/d3re00261f
|View full text |Cite
|
Sign up to set email alerts
|

The switch-off method: rapid investigation of flow photochemical reactions

Abstract: In a flow photochemical process switching off the light source and monitoring the reaction composition as it leaves the photoreactor allows the effect of all irradiation times up to a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In a similar way, switching off the light during photochemical reactions has been used to allow a single experiment to provide a continuous range of light exposure times. 24 A particularly powerful method, which has no equivalent with batch reactors, is to dynamically control the flow rate of several pumps in order to vary the concentration of a reagent component during a single experiment. 16,20 Continuous data on the effect of the concentration of the varied component is thus obtained, albeit at a single time point.…”
Section: Introductionmentioning
confidence: 99%
“…In a similar way, switching off the light during photochemical reactions has been used to allow a single experiment to provide a continuous range of light exposure times. 24 A particularly powerful method, which has no equivalent with batch reactors, is to dynamically control the flow rate of several pumps in order to vary the concentration of a reagent component during a single experiment. 16,20 Continuous data on the effect of the concentration of the varied component is thus obtained, albeit at a single time point.…”
Section: Introductionmentioning
confidence: 99%
“…47 Recently, Drelinkiewicz et al reported a new method for timesweep kinetics, specifically concerning photochemical reactions in which no flow rate change is applied, but after stabilisation of the reactor the light is simply turned off, thus creating a gradient of effective reaction time (by choosing irradiation time relative to reactor residence time), assuming no reaction takes place when the light is turned off. 48 Junkers and co-workers gave a recent overview of timesweep transient kinetic measurements in flow for polymer reaction monitoring 49 and used this platform to study the PI-RAFT polymerization of various methacrylic monomers and the effect of light intensity and trithiocarbonate RAFT agent on polymerization kinetics. 15 A lower target degree of polymerization and increased light intensity resulted in faster rates of polymerization of methyl methacrylate due to increased concentration and rate of photolysis of the RAFT agent, respectively.…”
Section: Introductionmentioning
confidence: 99%